2002
DOI: 10.1002/app.11322
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of polyurethane foams from soybean oil

Abstract: Modified soy-based vegetable oil polyols were successfully incorporated as a replacement for conventional polyols to produce flexible slabstock polyurethane foams. The oil was characterized for its hydroxyl value and fatty acid composition. The modified oils had higher hydroxyl values and lower unsaturated acids than regular unmodified oils. Three different modified polyols were used to investigate the reactivity with isocyanates. The effects on the foaming reaction of two different isocyanates, namely TDI and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
146
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 177 publications
(159 citation statements)
references
References 12 publications
4
146
0
Order By: Relevance
“…This value is clearly higher than the theoretically calculated value (M n ¼ 875.4 g/mol) and also than the value calculated from the saponification acid numbers assuming that the oil is monodisperse (M n ¼ 914.4 g/mol). John et al [12] have previously reported a large aberration in the SEC characterization of triglycerides. They worked with soy oil and although the polydispersity of the samples was very low (M w /M n ¼ 1.01), as it is the case in this work, the molar masses determined by this method almost doubled the actual masses of the triglycerides.…”
Section: Characterization Of the Tung Oil And Its Modificationsmentioning
confidence: 99%
“…This value is clearly higher than the theoretically calculated value (M n ¼ 875.4 g/mol) and also than the value calculated from the saponification acid numbers assuming that the oil is monodisperse (M n ¼ 914.4 g/mol). John et al [12] have previously reported a large aberration in the SEC characterization of triglycerides. They worked with soy oil and although the polydispersity of the samples was very low (M w /M n ¼ 1.01), as it is the case in this work, the molar masses determined by this method almost doubled the actual masses of the triglycerides.…”
Section: Characterization Of the Tung Oil And Its Modificationsmentioning
confidence: 99%
“…Vegetable oil-based polyols derived from oil seeds, such as sunflower, soybean, canola and rapeseed, were applied in PUR flexible foams synthesis [4,9,13,14]. These modifications had limited success and showed that partial incorporation of vegetable oil-based polyols is much more successful.…”
Section: Introductionmentioning
confidence: 99%
“…Polyurethanes are an important and very versatile class of polymer materials with desirable properties, such as high abrasion resistance, tears strength, excellent shock absorption, flexibility and elasticity (20)(21)(22) . The attractiveness of polyurethanes stems from their excellent bonding to different substrates, relatively low price and fast reaction time (23) .…”
Section: Resultsmentioning
confidence: 99%